Lysosome-related organelles as functional adaptations of the endolysosomal system. (August 2019) - Delevoye, Cédric; Marks, Michael S; Raposo, Graça
Abstract : Unique functions of specialised cells such as those of the immune and haemostasis systems, skin, blood vessels, lung, and bone require specialised compartments, collectively referred to as lysosome-related organelles (LROs), that share features of endosomes and lysosomes. LROs harbour unique morphological features and cell type-specific contents, and most if not all undergo regulated secretion for diverse functions. Ongoing research, largely driven by analyses of inherited diseases and their model systems, is unravelling the mechanisms involved in LRO generation, maturation, transport and secretion. A molecular understanding of these features will provide targets and markers that can be exploited for diagnosis and therapy of a myriad of diseases.